Subclinical doses of dietary fumonisins and deoxynivalenol cause cecal microbiota dysbiosis in broiler chickens challenged with Clostridium perfringens - Shanmugasundaram, Revathi; Lourenco, Jeferson; Hakeem, Walid Al; Dycus, Madison M.; Applegate, Todd J. (Frontiers in Microbiology, 2023)
Fusarium toxins are one of the most common contaminants in poultry diets. Cooccurrence of fumonisins (FUM) and deoxynivalenol (DON), even at a subclinical dose, negatively affects the growth performance, intestinal integrity and induce subclinical necrotic enteritis in broiler chickens. Loss of gut integrity can be expected to alter the intestinal microbiota composition. The objective of this study was to identify the effects of combined FUM and DON on the cecal microbiome profile and predicted metabolic functions and short chain fatty acid profile in broilers challenged with Clostridium perfringens. A total of 240 one-day-old chicks were randomly assigned to two treatments: a control diet, and the control diet with 3mg/kg FUM + 4 mg/kg DON each with eight replications. All the birds were received cocci vaccine at d0. All birds in both treatment groups were challenged with C. perfringens 1 X 108 CFU via feed on d19 and 20 to achieve 5% mortality. On d35, the FUM and DON contaminated diet numerically (P= 0.06) decreased the body weight gain (BWG) by 84g compared to the control group. The bacterial compositions of the cecal contents were analyzed by sequencing the V3–V4 region of the 16S rRNA gene. Overall, microbial richness and diversity increased (P < 0.02) during the studied period (d 21 – 35). When compared to the control group, the FUM + DON group's cecal contents had higher (P 0.05) microbial evenness and diversity (Shannon index) and lower relative abundance of Proteobacteria (P = 0.001). The abundance of Defluviitaleaceae and Lachnospiraceae families were lower (P < 0.05) in the ceca of control group birds, but the abundances of Moraxellaceae and Streptococcaceae were higher (P< 0.05). FUM and DON exposure decreased (P 0.05) Acinetobacter and Pseudomonas abundance and had a tendency (P = 0.08) to decrease Thermincola abundance when compared to the control group. In the ileum, no NE-specific microscopic abnormalities were found; however, the tip of the villi was compromised. The present findings showed that dietary FUM and DON contamination, even at subclinical levels, altered cecal microbial composition, and impaired the gut immune response, potentially predisposing the birds to necrotic enteritis.